Target Setting in Tournaments: Theory and Evidence from China. Issue 623 (20th May 2019) - Li, Xing; Liu, Chong; Weng, Xi; Zhou, Li-An
Abstract: Motivated by the prevalence of economic targets at all levels of territory administration in China, this article proposes a Tullock contest model to study optimal target setting in a multi-layered tournament-based organisation. In our model, targets are used by upper-level officials to convey the importance of economic growth and incentivise subordinates in the tournaments. Our model predicts a top-down amplification of economic growth targets along the jurisdiction levels, which explains the observed pattern in China. Using both provincial and prefectural-level data, we test the model predictions and find consistent evidence.